The role of optimism in improving subjective well-being in Islamic Boarding School Students - Ikromi, Ziyadi Ali; Hidayat, Novi; Rismawati, Rismawati (Priviet Social Sciences Journal, 2025)
Subjective well-being is a critical metric for assessing quality of life, particularly among students residing in Islamic boarding schools. It encompasses both life satisfaction and emotional experiences, serving as a vital indicator of positive mental health. This study aimed to examine the impact of optimism on students' subjective well-being. A quantitative research methodology was employed, involving 93 students aged 13 to 17 years from Islamic boarding schools. Data were collected using scales measuring optimism and subjective well-being. The analysis was conducted using simple linear regression, supplemented by assumption tests, including normality and linearity assessments. The results indicated a significant effect of optimism on subjective well-being, with a p-value of 0.000 (p < 0.01). These findings suggest that optimism exerts a highly significant influence on the subjective well-being of students in Islamic boarding schools.